Educator’s Horizontal Mismatch in Open and Distance Learning - Cahyadi, Ni Made Ayu Krisna; Prima, Suci Rahmawati; Sugiarti, Dian (LPPM Universitas Terbuka, 2024)
Open and distance learning (ODL) is more complex than conventional learning. Educators are required to have adequate soft skills and must be able to keep up with technological developments. The aim of this study is to examine the existence of educators’ horizontal mismatch in the ODL system and efforts to reduce the occurrence of this mismatch. Horizontal mismatch occurs due to a mismatch in the abilities of educators, whether the educator is over-qualified or under-qualified. This study was conducted on Universitas Terbuka tutors who have used ODL system since 1984. The results of this study show that tutors feel all their abilities are in line with university excpectations, but when carrying out teaching practice, university still found tutors who have difficulty in adapting to technological changes and have deficiencies in intrapersonal and interpersonal skills. Efforts that can be made are training to develop teaching material and soft skill, stricter supervision during the learning process, an official community of course lecturers, and the existence of team teaching between internal lecturers and tutors.